Organizational Support and Intrapersonal Competence as Determinants of Employee Performance at PDAM Tirta Darma Ayu Indramayu - Talita Paramesti Ardhani; Lisa Harry Sulistiyowati (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of organizational support and intrapersonal competence on employee performance at PDAM Tirta Darma Ayu Indramayu. This study used a quantitative approach with a descriptive and verificative research design. Primary data were collected through questionnaires distributed to 108 employees selected from a population of 147 employees using simple random sampling. The data were analyzed using SPSS version 23 through validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that organizational support has a positive and significant effect on employee performance, with a regression coefficient of 0.565 and a t-value of 4.772. Intrapersonal competence also has a positive and significant effect on employee performance, with a regression coefficient of 0.472 and a t-value of 7.412. Simultaneously, organizational support and intrapersonal competence significantly affect employee performance, as indicated by an F-value of 61.178 and an Adjusted R Square of 0.529. These findings suggest that PDAM management should strengthen organizational support systems and develop employees’ intrapersonal competence to improve service-oriented performance.